PENGARUH PENYULUHAN DENGAN MODUL TERHADAP PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PEMELIHARAAN KESEHATAN GIGI ANAK SEKOLAH DASAR 2022 - I Made Budi Artawa; I Gede Surya Kencana; I Nyoman Gejir (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
Dental and oral hygiene is influenced by tooth brushing behavior, tooth brushing behavior is influenced by the level of knowledge. The level of knowledge can be increased through counseling by utilizing the media. However, it is not yet known whether counseling with media modules can increase teeth brushing knowledge and skills. The purpose of this study was to determine the effect of counseling with media modules on increasing knowledge and teeth brushing skills of SD Negeri 1 Batur students. Experimental community trial design with pretest-posttest only group design. The research was conducted at SD N.1 Batur in May-June 2022. The total sample was 187 people. The research procedure was carried out by pre-test, tooth brushing observation, dental health maintenance counseling and tooth brushing knowledge and skills post-test. Data were analyzed statistically with the help of a computer (SPSS). The results are presented in the form of narration and tables and then conclusions are drawn. The results of the study found that before being given counseling on dental health maintenance, the level of knowledge was at most in the failure criteria as many as 112 people (59.89%) and at least in the good criteria as many as 11 people (5.88%). After being given the most knowledge level intervention in very good criteria as many as 146 people (78.07%) and at least in the less criteria and failed each one person (0.53%). Tooth brushing skills at the target before the intervention were most in the category needing guidance as many as 154 people (82.35%) and the least in the good category was one person (0.53%). Tooth brushing skills after the intervention were mostly in the very good category with 183 people (97.86%) and none got the good category or needed guidance (0%). The results of statistical analysis of the level of knowledge, teeth brushing skills before and after counseling and brushing practice, with the Paired Samples t-test analysis showed that the value of p = 0.000 is less than 0.05. which means counseling has an influence on increasing knowledge and skills of brushing teeth. In conclusion, there is a significant effect of counseling with modules on increasing knowledge and skills of brushing teeth in students of SD N 1 Batur, Kintamani District, in 2022.